Obstacles that faced teaching swimming courses at Faculty of Physical Education and Sport Science at Hashemite University during Corona pandemic from the students' point of view themselves - Abed albasit Mobarak alShorman; Faleh Sultan Abu Eid; Neila Muhammad Ghannouchi (University of Basrah, 2024)
This study aimed to identify the obstacles that faced teaching swimming courses at Faculty of Physical Education and Sport Science at Hashemite University during Corona pandemic from the perspective of the students themselves The researchers used the descriptive approach for its suitability to the nature of the study and its objectives, where the questionnaire was used as a tool to obtain the study data after the researchers conducted validity and reliability transactions to ensure their safety and suitability for the current study،The results of the study indicated that the most important obstacles that faced teaching swimming courses at the Faculty of Physical Education and Sports Sciences at the Hashemite University during the Corona pandemic were arranged as following: Obstacles related to the electronic field, obstacles related to the academic field, obstacles related to the psychological field, Obstacles related to the economic field, and finally obstacles related to the social field؛The researchers recommend generalizing the results of this study to benefit from them in knowing the nature of the obstacles that students of practical courses faced, especially swimming during Corona pandemic